Long-Term Survival in Locally Advanced KRAS Wild-Type Pancreatic Adenocarcinoma - Marion Alhenc-Gelas; Romain Cohen; Pascale Cervera; Jean-Christophe Vaillant; Thierry André (Case Reports in Gastrointestinal Medicine)
Pancreatic adenocarcinoma remains a cancer associated with a poor prognosis. For locally advanced pancreatic cancer (LAPC), median overall survival is approximately 16 months. Here we report the case of a 52-year-old LAPC patient treated with chemotherapy followed by chemoradiotherapy that was associated with a 14-year complete remission. A peritoneal relapse was then observed and chemotherapy was undergone until the patient died of infectious complications, 17 years after his diagnosis. The tumor was found KRAS, TP53, BRCA1, and BRCA2 wild-type. This KRAS wild-type LAPC-long survivor case report emphasizes the need to develop molecular approaches to predict LAPC patients’ prognosis.